2007
DOI: 10.1115/1.2755063
|View full text |Cite
|
Sign up to set email alerts
|

Internal Condensing Flows inside a Vertical Pipe: Experimental/Computational Investigations of the Effects of Specified and Unspecified (Free) Conditions at Exit

Abstract: Reported experimental and computational results confirm that both the flow features and heat-transfer rates inside a condenser depend on the specification of inlet, wall, and exit conditions. The results show that the commonly occurring condensing flows’ special sensitivity to changes in exit conditions (i.e., changes in exit pressure) arises from the ease with which these changes alter the vapor flow field in the interior. When, at a fixed steady mass flow rate, the exit pressure is changed from one steady va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Examples of flow type (B) are fully condensing flows in microgravity or certain condensing flows in horizontal test sections (e.g., flows of the type shown earlier in Figure 3 with x e > x** or x*≈ 0 because ). According to first‐principle‐based theory and supporting computational results, 1 these condensing flows simply cannot occur (over a range of inlet flow rates and duct lengths) in microgravity by self‐selection of a steady exit pressure.…”
Section: Exit Condition Parameter ϕ and Its Role In Interpreting Resumentioning
confidence: 89%
See 3 more Smart Citations
“…Examples of flow type (B) are fully condensing flows in microgravity or certain condensing flows in horizontal test sections (e.g., flows of the type shown earlier in Figure 3 with x e > x** or x*≈ 0 because ). According to first‐principle‐based theory and supporting computational results, 1 these condensing flows simply cannot occur (over a range of inlet flow rates and duct lengths) in microgravity by self‐selection of a steady exit pressure.…”
Section: Exit Condition Parameter ϕ and Its Role In Interpreting Resumentioning
confidence: 89%
“…Any other Δp =Δp f value can be fixed (see Δp f corresponding to point E above) with the help of operating procedure O‐2. This is because, for the specified exit condition cases (for category I flows in Narain et al 1 ), the Δp f value can be fixed at an arbitrary value and is not required to lie on any particular curve. ( B ) The system and subsystem curves for the condensing flow arrangement in Figure 13B.…”
Section: Exit Condition Parameter ϕ and Its Role In Interpreting Resumentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the elliptical section tube has a clear improvement of the vapor condensation over horizontal cylinder. Recently, the stability of the condensing flows has been discussed numerically and experimentally in several works [23][24][25][26][27]. The effect of the free-stream vapor-striking angle on the condensation over a vertical plate was analyzed by Khaled et al [28].…”
Section: Introductionmentioning
confidence: 99%